Siolimbona dan Martabat Tujuh: Warisan Demokrasi Lokal Kesultanan Buton sebagai Sumber Belajar Pendidikan Pancasila dan Kewarganegaraan - Nuraisyah; Karmila; Suci Ramadani; I luh Darmayanti; Muh. Sastro Aryanto; Rahma Daniati; Putu Meliana Putri; Jasrudin; Amisbah Ramly; Sri Hariati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the cultural values ​​and governance system of the Buton Sultanate and their relevance to Pancasila and Civic Education (PPKn). The study focuses on the cultural heritage of the Buton Sultanate, the *Martabat 7* concept as a philosophical foundation for governance, the *musyawarah*-based (deliberative) sultan election system, and the Museum of the Last Sultan of Buton as a medium for historical preservation. A qualitative approach was employed, utilizing a field study method conducted in the Buton Palace (Keraton) area of ​​Baubau City, Southeast Sulawesi. Data collection involved observation, documentation, and semi-structured interviews with informants knowledgeable about the history and culture of the Buton Sultanate. Data were analyzed using thematic analysis, with Pancasila values ​​and PPKn principles serving as the analytical framework. The results indicate that the cultural heritage of the Buton Sultanate possesses not only historical value but also embodies values ​​of deliberation, justice, leadership, religiosity, and social responsibility—all of which align with Pancasila values, particularly the second, fourth, and fifth principles. The *Martabat 7* concept demonstrates an integration of Islamic teachings and governance, emphasizing moral integrity and a balance between citizens' rights and obligations. The sultan election system via the *Siolimbona* reflects a local democratic practice rooted in deliberation, while the Museum of the Last Sultan of Buton holds potential as a contextual learning resource for civic education, despite requiring more optimal management. This study affirms that the cultural heritage of the Buton Sultanate serves as an authentic learning resource capable of strengthening character education, national identity, and historical awareness within PPKn instruction.